Analysing Digital Trails for Targeted Digital Marketing - Jose, Siddharth (Digital Repository of Theses - SSBM Geneva, 2025)
Digital trails offer significant potential for enhancing marketing strategies, though their utility in Switzerland is often limited by strict data privacy regulations. This study aimed to establish a framework for leveraging digital trail analysis to provide startups with a competitive marketing advantage. Using an exploratory research design and mixed-methods approach, data were collected via structured questionnaires and semi-structured interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative responses underwent thematic analysis. Findings indicate a strong positive correlation between digital trail analysis and improvements in return on investment (ROI), customer engagement, and overall marketing effectiveness. The study also found that incorporating personalization and relevance into digital marketing strategies significantly strengthens this relationship. Furthermore, integrating consumer psychology and product market research allowed deeper insights into customer motivations, enabling improved targeting, segmentation, and product innovation. Competitor feedback and content marketing strategies were shown to enhance marketing approaches by aligning better with customer needs and optimizing resource allocation. These insights suggest that data-driven decision-making, underpinned by digital trail analysis, can play a pivotal role in elevating the performance of Swiss startups. In conclusion, the research supports the use of digital trail analysis as a practical and effective tool for market analysis in environments with stringent data constraints. Startups that adopt goal-oriented digital trail strategies are likely to experience measurable improvements in ROI, customer engagement, and marketing effectiveness. Future research could benefit from a larger sample size, particularly by including more marketing professionals, to validate and expand on these findings.